Pengaruh Sertifikasi Halal dan Inovasi Produk terhadap Kinerja Pemasaran UMKM Makanan dan Minuman di Kecamatan Dlanggu Kabupaten Mojokerto - Muhammad Haris Muhasibi; Abdillah Mundir; Ifdlolul Maghfur (Jurnal Ilmiah Ekonomi Islam, 2026)
The dynamics of the food and beverage industry require Micro, Small, and Medium Enterprises (MSMEs) to balance compliance with religious regulations and business innovation strategies. This study aims to investigate the impact of Halal Certification and Product Innovation on Marketing Performance among MSME actors in the food and beverage sector in the Dlanggu District area. Utilizing a quantitative approach and survey methods, primary data were gathered from 99 business respondents determined through a purposive sampling technique. Hypothesis testing was carried out using multiple linear regression analysis in SPSS. The research findings partially support the view that the ownership of Halal Certification provides a significant positive contribution to boosting local marketing performance. On the other hand, the aspect of Product Innovation does not show a significant effect on marketing achievements. Even so, when tested simultaneously, the interaction between Halal Certification and Product Innovation variables proved to have a very significant influence, contributing 72.7% to variations in marketing performance. This research emphasizes that, for the characteristics of suburban consumers, the presence of innovation in new products will receive a positive response and be absorbed by the market only if it is supported by a valid guarantee of halal legality.